Psychiatric traits and intracerebral hemorrhage: A Mendelian randomization study - Wang, Qingduo; Qi, Yajie; Li, Yuping; Yan, Zhengcun; Wang, Xiaodong; Ma, Qiang; Tang, Can; Liu, Xiaoguang; Wei, Min; Zhang, Hengzhu (Frontiers in Psychiatry, 2023)
Abstract Background: Psychiatric traits have been associated with intracerebral hemorrhage (ICH) in observational studies, although their causal relationships remain uncertain. We used Mendelian randomization analyses to infer causality between psychiatric traits and ICH. Methods We collected data from genome-wide association studies of ICH (n = 361,194) and eight psychiatric traits among Europeans, including mood swings (n = 451,619), major depressive disorder (n = 480,359), attention-deficit/hyperactivity disorder (n = 53,293), anxiety (n = 459,560), insomnia (n = 462,341), schizophrenia (n = 77,096), neuroticism (n = 374,323), and bipolar disorder (n = 51,710). We performed a series of bidirectional two-sample Mendelian randomization and related sensitivity analyses. A Bonferroni corrected threshold of p < 0.00625 (0.05/8) was considered to be significant, and P<0.05 was considered suggestive of evidence for a potential association. Results: Mendelian randomization analyses revealed suggestive positive causality of mood swings on ICH (odds ratio = 1.006, 95% confidence interval = 1.001–1.012, p = 0.046), and the result was consistent after sensitivity analysis. However, major depressive disorder (p = 0.415), attention-deficit/hyperactivity disorder (p = 0.456), anxiety (p = 0.664), insomnia (p = 0.699), schizophrenia (p = 0.799), neuroticism (p = 0.140), and bipolar disorder (p = 0.443) are not significantly associated with the incidence of ICH. In the reverse Mendelian randomization analyses, no causal effects of ICH on mood swings (p = 0.565), major depressive disorder (p = 0.630), attention-deficit/hyperactivity disorder (p = 0.346), anxiety (p = 0.266), insomnia (p = 0.102), schizophrenia (p = 0.463), neuroticism (p = 0.261), or bipolar disorder (p = 0.985) were found. Conclusions: Our study revealed that mood swings are suggestively causal of ICH and increase the risk of ICH. These results suggest the clinical significance of controlling mood swings for ICH prevention.